Investigating and Evaluating Computer Sciences ESP Syllabus in Tabouk University, Saudi Arabia. - Mohamed, Omaymah Elkheir; Ahmed, Ahmed Gasm Alseed (Advances in Social Sciences Research Journal, 2020)
This paper is conducted to investigate and evaluate the ESP computer sciences syllabus in Tabuk University Saudi Arabia. The samples are 80 students of ESP and 15 computer sciences teachers. To collect data, the researchers used questionnaires and an interview .The paper adopted the descriptive analytical approach. For data analysis, the researchers used the computer program (SPSS). The findings showed that the computer sciences ESP syllabus is not based on the students needs , it also showed that the ESP syllabus lacks the strategic objectives. The ESP syllabus is not efficient enough to bridge the gap between English for academic purpose and English for occupational purpose. . Therefore, the researchers recommend taking students needs into account when setting the computer sciences syllabus , involving strategic objectives in the syllabus and establishing sufficient computer sciences goals.